A young child formula supplemented with a synbiotic mixture of scGOS/lcFOS and Bifidobacterium breve M-16V improves the gut microbiota and iron status in healthy toddlers - Chew, Charmaine; Matsuyama, Misa; Davies, Peter S. W.; Hill, Rebecca J.; Morrison, Mark; Martin, Rocio; Codoñer, Francisco M.; Knol, Jan; Roeselers, Guus (Frontiers in Pediatrics, 2024)
Early-life gut microbiota development depends on a highly synchronized microbial colonization process in which diet is a key regulator. Microbiota transition toward a more adult-like state in toddlerhood goes hand in hand with the transition from a milk-based diet to a family diet. Microbiota development during the first year of life has been extensively researched; however, studies during toddlerhood remain sparse. Young children's requirement for micronutrients, such as dietary iron, is higher than adults. However, their intake is usually sub-optimal based on regular dietary consumption. The Child Health and Residence Microbes (CHaRM) study, conducted as an adjunct to the GUMLi (Growing Up Milk “Lite”) trial, was a double-blind randomized controlled trial to investigate the effects on body composition of toddler milk compared to unfortified standard cow's milk in healthy children between 1 and 2 years of age in Brisbane (Australia). In this trial, fortified milk with reduced protein content and added synbiotics [Bifidobacterium breve M-16V, short-chain galactooligosaccharides, and long-chain fructooligosaccharides (ratio 9:1)] and micronutrients were compared to standard unfortified cow's milk. In the present study, the effects of the intervention on the gut microbiota and its relationship with iron status in toddlers were investigated in a subset of 29 children (18 in the Active group and 11 in the Control group) who completed the CHaRM study. The toddler microbiota consisted mainly of members of the phyla Firmicutes, Bacteroidota, and Actinobacteriota. The abundance of the B. breve species was quantified and was found to be lower in the Control group than in the Active group. Analysis of blood iron markers showed an improved iron status in the Active group. We observed a positive correlation between Bifidobacterium abundance and blood iron status. PICRUSt, a predictive functionality algorithm based on 16S ribosomal gene sequencing, was used to correlate potential microbial functions with iron status measurements. This analysis showed that the abundance of predicted genes encoding for enterobactin, a class of siderophores specific to Enterobacteriaceae, is inversely correlated with the relative abundance of members of the genus Bifidobacterium. These findings suggest that healthy children who consume a young child formula fortified with synbiotics as part of a healthy diet have improved iron availability and absorption in the gut and an increased abundance of Bifidobacterium in their gut microbiome.